THE EFFECT OF NON-PHYSICAL WORK ENVIRONMENT, COMPETENCE ON EMPLOYEE ENGAGEMENT MEDIATED BY JOB SATISFACTION - Marina Fadilah; Sulaiman Helmi (SEAN Institute, 2023)
The purpose of this study was to analyze the direct effect of the non-physical work environment, competency on employee engagement mediated by job satisfaction, the object of research was PT. Semen Baturaja Palembang, the sample of this study were employees at PT. Semen Baturaja Palembang, with a total of 111 employees, the method used is a quantitative method with the SEM-Smart-PLS analysis technique. The data used are primary and secondary data, hypothesis testing using weight relations. Results on job satisfaction, competence has a positive and significant effect on job satisfaction, non-physical work environment is positive but not significant on employee engagement, competence has a positive and significant effect on employee engagement, non-physical work environment is positive but not significant on employee engagement mediated by job satisfaction , positive and significant competency on employee engagement is mediated by job satisfaction.